1975
DOI: 10.1111/j.1464-410x.1975.tb06257.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlorhexidine Irrigation of the Bladder in the Rat

Abstract: Rats' bladders were irrigated with aqueous solutions of chlorhexidine digluconate 1 : 5,000 or 1 : 10,000 for varying periods up to 48 hours. Histologic examination of the bladders showed severe erosive cystitis in a high percentage of cases. It is concluded that chlorhexidine cannot be recommended for prolonged irrigation of the bladder or for instillation during the intermittent catheterisation where chlorhexidine has repeated and prolonged contact with bladder mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…The increased exfoliation followed washouts with physiological saline, noxythiolin and chlorhexidine. Previous studies using animal models have demonstrated that various irrigants may result in erosive cystitis after contact for several hours with the bladder mucosa surface (Harper and Matz, 1975). Whilst this may conceivably have contributed to the present findings, particularly with the noxythiolin and chlorhexidine, the response to normal saline, and the rapidity of the resulting increase in exfoliation which occurred immediately after bladder irrigation, suggest that the physical forces of the irrigations resulted in removal of cell sheets from an already damaged urothelium.…”
Section: Discussionsupporting
confidence: 47%
“…The increased exfoliation followed washouts with physiological saline, noxythiolin and chlorhexidine. Previous studies using animal models have demonstrated that various irrigants may result in erosive cystitis after contact for several hours with the bladder mucosa surface (Harper and Matz, 1975). Whilst this may conceivably have contributed to the present findings, particularly with the noxythiolin and chlorhexidine, the response to normal saline, and the rapidity of the resulting increase in exfoliation which occurred immediately after bladder irrigation, suggest that the physical forces of the irrigations resulted in removal of cell sheets from an already damaged urothelium.…”
Section: Discussionsupporting
confidence: 47%
“…Chlorhexidine is an effective local urinary antiseptic (Gillespie et al, 1962) with low toxicity. Haematuria has been reported after its use as a bladder irrigant and prolonged instillation can cause erosive cystitis in rats (Harper and Matz, 1975). However, side effects were observed in only 3 patients in the present study and in only one patient did its use have to be stopped, despite using a higher concentration in this trial than is usual (1 : 2000-0.05%).…”
Section: Discussioncontrasting
confidence: 58%
“…In addition to this there have been 2 further reports (MacFadyen and Simmons, 1968;Pearman, 1971) of a 1 : 5000 aqueous solution of chlorhexidine digluconate causing frank haernaturia. Also, Harper and Matz (1975) demonstrated severe erosive reactions in rats after 24 to 48 hours' irrigation with chlorhexidine at 0.01 070. However, they suggested that it may be used, since many procedures are brief and non-repetitive, unlike frequent intermittent catheterisation for several weeks following acute spinal cord trauma.…”
Section: Chlorhexidine Digluconatementioning
confidence: 90%